Genetic diversity and recombination analysis of NADC34-like porcine reproductive and respiratory syndrome viruses - Ye, Z.; Wang, W.; Zhu, Z.; Wen, W.; Hu Suk Lee; Li, X. (Elsevier, 2026)
Highlights • Recombinant variants represent a substantial proportion (56.8%) of the analyzed NADC34-like PRRSV strains. • 12 consistent recombinant patterns (R1-R12) were defined across 176 NADC34-like whole-genome sequences. • Recombination hotspots in Chinese strains shifted from structural genes to ORF1a after 2020. • Lineage 1.8 is the primary minor parent driving NADC34-like genetic diversification.